2010
DOI: 10.1002/pola.23964
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and field‐effect transistor performance of poly[2,6‐bis(3‐tridecanoxythiophen‐2‐yl)benzo[1,2‐b;4,5‐b′]dithiophene]

Abstract: A new copolymer of benzo [1,2-b:4,5-b 0 ]dithiophene and 3,3 0 -bis(tridecanoxy)-5,5 0 -bithiophene was synthesized through Stille copolymerization. The bis-(3-alkoxythiophene) monomer was synthesized through a silver fluoride mediated, palladium-catalyzed cross-coupling, in which bromide functional groups were preserved instead of consumed. The copolymer has been characterized and applied in field-effect transistors, giving a hole mobility of 2 Â 10 À3 cm 2 /Vs and an on/off ratio >10 6 , with negligible hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These new materials, also called synthetic metals, can reach high electrical conductivity, very close to the value of some metals and offer an extensive possibility to modify the surface of conventional electrodes supplying fascinating properties [17]. It was found that they can be used in many areas, such as electrochromic materials [18], organic-based solar cells [19,20], organic field effect transistors [21,22] and organic light-emitting diodes [23,24]. Moreover, providing simplicity and high reproducibility in preparation, easiness in arranging the thickness of the film, compatibility with biological molecules, and possibility to produce at room temperature make electrochemically synthesized CPs charming in designing biosensors [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These new materials, also called synthetic metals, can reach high electrical conductivity, very close to the value of some metals and offer an extensive possibility to modify the surface of conventional electrodes supplying fascinating properties [17]. It was found that they can be used in many areas, such as electrochromic materials [18], organic-based solar cells [19,20], organic field effect transistors [21,22] and organic light-emitting diodes [23,24]. Moreover, providing simplicity and high reproducibility in preparation, easiness in arranging the thickness of the film, compatibility with biological molecules, and possibility to produce at room temperature make electrochemically synthesized CPs charming in designing biosensors [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The difference of optical band gap is particularly owed to the different molecular structures and the number of electron donating functional groups. [42,43] Both of them have relatively small band gap, so the electron transition is easy to occur. It is suitable for the applications in photoelectric materials, especially for O1.…”
Section: Uv-vis Absorption and Fluorescence Emission Spectramentioning
confidence: 99%
“…Organic semiconductors have attracted considerable scientific and industrial interest for applications in organic electronics and optoelectronics including organic field‐effect transistors (OFETs),1–14 organic light emitting diodes (OLEDs),15–18 and organic photovoltaic cells (OPVs) 12, 19–23. In particular, polymer semiconductors have been widely studied because of their unique advantages such as chemical tunability, compatibility with plastic substrates, structural flexibility, and favorable solution processability (ink‐jet printing and roll‐to‐roll process) 6, 24–26…”
Section: Introductionmentioning
confidence: 99%